ON THE LAW OF PLANETARY DISTANCES IN THE SOLAR SYSTEM - Bezdenezhnyj, V. P. (Одеські астрономічні публікації, 2007)
Representations of major semiaxes of planets and distances of nearby planets by means of degrees of two and prime numbers are made. We analyse different formulas for these representations and give new formulas (3)-(4) and a system of formulas (6)-(8) which by the best appearance presents all the planets of the Planetary system, including Neptune and Pluto. Recommendations are given for the search of the tenth planet (instead of Pluto) and eleventh one.